ZR-IN-RUTILE THERMOMETRY IN BLUESCHISTS FROM SIFNOS, GREECE - Spear F.S.; Wark D.A.; Cheney J.T.; Schumacher J.C.; Watson E.B. (My University, 2006)
Zr-in-rutile thermometry on samples of blueschist from Sifnos, Greece, yields temperatures that reflect progressive crystallization of rutile from ca. 445 to 505°C with an analytical precision of + 18/−27 and ± 10°C using the electron microprobe and ± 1.5–3.5°C using the ion microprobe. Individual grains are generally homogeneous within analytical uncertainty. Different grains within a single sample record temperature differences as large 55°, although in most samples the range of temperatures is on the order of 25°. In several samples, Zr-in-rutile temperatures from grains within garnet are lower than temperatures from matrix grains, reflecting growth of rutile with increasing temperature of metamorphism. Although the specific rutile-producing reactions have not been identified, it is inferred that rutile grows from either continuous reaction involving the breakdown of lower grade phases (possibly ilmenite), or from pseudomorph reactions involving the breakdown of relic igneous precursors at blueschist-facies conditions. No systematic variation in rutile temperatures was observed across the blueschist belt of northern Sifnos, consistent with the belt having behaved as a coherent block during subduction.
Keywords: RUTILE; THERMOMETRY; BLUESCHIST; CYCLADES; SIFNOS